Pengaruh Product Completeness, Service Quality, Dan Word Of Mouth Terhadap Keputusan Pembelian (Studi Pada Deliwafa Store Malang) - Nofita, Dyah; Nurhajati, Nurhajati; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The purpose of this study was determine product completeness, service quality, and word of mouth on purchasing decisions partially or simultaneously. This research method uses quantitative research methods and this type of research is purposive sampling. The sample of this research is Deliwafa Store Malang consumers with a total of 90 respondents. To obtain accurate and detailed data, this study used a data collection method with a questionnaire. The data analysis used is instrument test, normality test, classical assumptions, multiple linear regression analysis, hypothesis testing, and the coefficient of determination using the help of SPSS 25. The results of this study indicate that product completeness, service quality, and word of mouth simultaneously have a significant effect on purchasing decisions at Deliwafa Store Malang. Furthermore, partially, product completeness, service quality, and word of mouth have a positive and significant effect on purchasing decisions at Deliwafa Store Malang. Keywords: Product Completeness, Service Quality, Word of Mouth